P153 Managing Suspected Pulmonary Embolism: Applying an effective ambulatory emergency care strategy. (14th November 2013) - Varia, R; Murthy, M; Pocock, A; Abbas, M
Abstract : Background: We observed a high number of patients admitted with suspected pulmonary embolism (PE) via our acute medical unit. After positive diagnosis, they remained as inpatients until their International Normalised Ratio (INR) was in range resulting in long lengths of stay - Median (range) 7 (0 to 52) days. Recently, there has been increasing interest in ambulatory management providing high quality cost-effective care. Objectives: To develop a care pathway for suspected PE incorporating prognostic scoring to assist ambulatory same-day management. To assess cost effectiveness of such a strategy in terms of bed day release whilst ensuring that it did not adversely affect safety by misclassification of patients. Method: We formulated an ambulatory pathway (figure1 ) with an algorithm comprising of the simplified PESI (pulmonary embolism severity index) score and serum Troponin I measurement with various exclusion criteria to identify patients fit for ambulatory management. Over a 3-month period, 191 patients underwent computerised tomography pulmonary angiogram (CTPA) for suspected PE. 28/191 patients were excluded from analysis as they were outpatients or pre-existing inpatients. We retrospectively applied the pathway to the remaining 163 patients. To assess the impact of the pathway, we measured increase in the number of patients that could have been managed using same-day emergency care, incremental bed day release and benefits derived via the enhanced tariff through Payment by Results (PbR). Safety was assessed by noting mortality within the ambulatory group identified. Results: 73/163 (44%) patients were male and mean (SD) age was 62 (17.8) years. Using our pathway, 36/163 (22%) of all suspected PEs could have been managed within a zero-day admission. 5/36 (14%) with a definite PE could have been managed as ambulatory patients. A mean incremental stay of 4 days for the 36 patients equates to 144 bed days released over the 3-month period. The PbR additional income on completion of a same-day emergency management would add £225/patient to savings made. None of the patients selected for ambulatory management via the pathway suffered any adverse events. Conclusion: We have successfully developed and implemented an effective ambulatory management strategy for suspected PE. A validity study is planned.